Dietary Factors Associated with Dental Erosion: A Meta-Analysis - Li, Haifeng; Zou, Yan; Ding, Gangqiang (PLOS ONE, 2012)
Background Some diet factors are risk factors for dental erosion. Methods We performed computer searches of PubMed, Cochrane Library, EBSCO, CALIS, et al., to search for studies investigating risk factors for dental erosion. For risk factors investigated in a comparative way, we computed pooled odds ratios (ORs) using the Mantel and Haenszel method. Results A total of 9 studies met the inclusion criteria, and 6 risk factors were considered, including soft drinks, sports drinks, juice, vitamin C, milk, and yoghourt. The following associations were found for soft drinks (OR = 2.41, 95%CI = 2.03–2.85) and vitamin C (OR = 1.16, 95%CI = 1.10–1.22). While juice (OR = 0.90, 95%CI = 0.25–3.24), sports drinks (OR = 1.58, 95%CI = 0.88–2.85), milk (OR = 0.67, 95%CI = 0.11–4.01), and yoghourt products (OR = 1.05, 95%CI = 0.28–3.96) were not associated with dental erosion. Conclusions This meta-analysis provides comprehensive evidence-based assessment of diet-related factors for dental erosion. Preventive strategies should be taken to reduce dental erosion.